2011
DOI: 10.2119/molmed.2011.00115
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Gene Products and Molecular Pathways Altered in Prostate Cancer- and Metastasis-Initiating Cells and Their Progenies and Novel Promising Multitargeted Therapies

Abstract: Recent gene expression profiling analyses and gain-and loss-of-function studies performed with distinct prostate cancer (PC) cell models indicated that the alterations in specific gene products and molecular pathways often occur in PC stem/progenitor cells and their progenies during prostate carcinogenesis and metastases at distant sites, including bones. Particularly, the sustained activation of epidermal growth factor receptor (EGFR), hedgehog, Wnt/β-catenin, Notch, hyaluronan (HA)/CD44 and stromal cell-deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 205 publications
(330 reference statements)
3
34
0
Order By: Relevance
“…In the present study we found that there was a high correlation between tumour pAkt-IR and pEGFR-IR scores, confirming the study of Koumakpayi et al [17], and consistent both with the finding of a high (54%) co-expression of EGFR and pAkt in prostate tumour cells [10] and the known signalling interrelationship between these two parameters [19]. We have additionally been able to show using partial multiple regression analyses that this correlation is not due to a “third-party” correlation with either the Gleason score or Ki67-IR.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study we found that there was a high correlation between tumour pAkt-IR and pEGFR-IR scores, confirming the study of Koumakpayi et al [17], and consistent both with the finding of a high (54%) co-expression of EGFR and pAkt in prostate tumour cells [10] and the known signalling interrelationship between these two parameters [19]. We have additionally been able to show using partial multiple regression analyses that this correlation is not due to a “third-party” correlation with either the Gleason score or Ki67-IR.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, HGF-induction of CXCL1 is completely consistent with reports that its expression is increased in high grade PCa [42], and that its product increases PCa cell migration and invasion [43], as well as PCa metastasis and chemoresistance [44,45]. HGF-induction of CXCR4 is consistent with reports that its product promotes metastasis in PCa [46,47] and other cancers where exogenous CXCL12 is available [48]. Similar to the multifaceted role of many inflammatory cytokines in cancer, Interferon alpha receptor 1 (IFNAR1) can mediate inflammation associated with PCa progression [49], but can also enable increased infiltration of T-and NK cells so as to prevent tumor de-differentiation and progression [50], suggesting that HGF-induction of IFNAR1 will have context dependent effects on cell migration and/or tumor metastasis.…”
Section: Analysis Of Hgf Motogenic Signaling By Gene Expression Profisupporting
confidence: 89%
“…Thus combinatorial targeting is a rational approach and may include both direct epithelial compartment targeting with cytotoxic agents and stromal-epithelial inhibition necessary to achieve maximised benefit [22, 23]. …”
Section: Discussionmentioning
confidence: 99%